2006
DOI: 10.1140/epjc/s2006-02584-8
|View full text |Cite
|
Sign up to set email alerts
|

New realizations of Lie algebra kappa-deformed Euclidean space

Abstract: We study Lie algebra κ-deformed Euclidean space with undeformed rotation algebra SO a (n) and commuting vectorlike derivatives. Infinitely many realizations in terms of commuting coordinates are constructed and a corresponding star product is found for each of them. The κ-deformed noncommutative space of the Lie algebra type with undeformed Poincaré algebra and with the corresponding deformed coalgebra is constructed in a unified way. 1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
335
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(349 citation statements)
references
References 34 publications
2
335
0
Order By: Relevance
“…Furthermore it has been shown that the space-times associated with a variety of black holes at the Planck scale could be described by a κ-Minkowski algebra [16][17][18]. In this paper we shall take the κ-Minkowski algebra [19][20][21][22][23][24][25][26][27][28] as the prototype of a space-time at the Planck scale and shall investigate various features of QNM's and associated physics in that background.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it has been shown that the space-times associated with a variety of black holes at the Planck scale could be described by a κ-Minkowski algebra [16][17][18]. In this paper we shall take the κ-Minkowski algebra [19][20][21][22][23][24][25][26][27][28] as the prototype of a space-time at the Planck scale and shall investigate various features of QNM's and associated physics in that background.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is a continuation of earlier work [6,7], following [8], whose aim is systematically to construct κ-deformed quantum field theory from the following particular perspective. (Other approaches can be found in [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].) We recall the viewpoint on quantum field theory taken by Weinberg in [25], namely that quantum field theory takes the form it does because this is essentially the only way to construct a quantum mechanical theory of point particles with Poincaré symmetry -given only a very limited number of additional physical principles, like cluster decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this more general class is provided by the κ-deformed space [3,4,5], which is based on a Lie algebra type noncommutativity. Apart from its algebraic aspects [6,7,8,9,10,11], various features of field theories and symmetries on κ-deformed spaces have recently been studied [12,13,14,15,16]. Such a space has also been discussed in the context of doubly special relativity [17,18,19].…”
mentioning
confidence: 99%